2019
DOI: 10.3390/coatings9120850
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Bilayer Titanium Silicate (TS-1) Zeolite Membranes by Periodical Secondary Growth

Abstract: A facile periodical secondary growth method, based on conventional secondary growth, is proposed to prepare bilayer TS-1 membranes. The novel periodical secondary growth consists of two or several periods, which involve three steps: the temperature is programmed to a desired crystallization temperature as the first stage, followed by holding for a certain duration, and finally cooling to room temperature. This periodical crystallization model enables a bilayer TS-1 membrane to be produced, while the convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It is the highest crystallization and most stable phase of all crystalline alumina. α-Al 2 O 3 possesses a variety of superior properties, like excellent mechanical properties, strong corrosion resistance, high temperature resistance, prominent insulation, etc., widely applied in wear resistance of polymer materials, ceramic materials, refractory materials, abrasives, ceramic substrates, and optical materials [9][10][11][12][13][14][15] . It has been recently found that a-Al 2 O 3 assumes unique advantages as the catalyst carrier due to its inertness at high temperatures, especially, catalytic properties of the support phase being not impeded [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…It is the highest crystallization and most stable phase of all crystalline alumina. α-Al 2 O 3 possesses a variety of superior properties, like excellent mechanical properties, strong corrosion resistance, high temperature resistance, prominent insulation, etc., widely applied in wear resistance of polymer materials, ceramic materials, refractory materials, abrasives, ceramic substrates, and optical materials [9][10][11][12][13][14][15] . It has been recently found that a-Al 2 O 3 assumes unique advantages as the catalyst carrier due to its inertness at high temperatures, especially, catalytic properties of the support phase being not impeded [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%